The Armenian Genocide. Unpunished Crimes - Grigorian, Vahagn (Genocidas ir rezistencija, 2005)
The Armenian genocide in 1915 was implemented as a result of Turkey’s genocidal policy of Turkey towards the non-Muslim nations. As early as in 1894–1896, over 300,000 thousand Armenians people shot by the order of the sultan Abdul Gamid. Nearly the same number of people were forced to accept Islam or found asylum in Persia and in East Armenia. The deserted lands were settled by Muslims. The party of Young Turks Ittihad ve Terakki (Unity and Progress), having organised the state takeover in 1908 and having seized power, replaced the pan-Islamism of the sultans by pan- Turanism. However, the Armenian nation, which for three thousand years had been living on the territory between the Turks and their eastern brothers, was an obstacle to realising the "high ideal of Turanism". In October 1914, during the sitting of the Cabinet of the Minister of the Interior, Talaat established a special organ, the Implementation Committee of the Three (Nazim, Beahetdin, Shakir, Shyukri) which was assigned the task of persecuting the Armenian nation. Leaders of the Young Turks considered that the war provided a convenient opportunity to implement such a policy. They organised special troops, the Teshkilati-i makhsuse (Special organisation), made up mostly of criminals released from prisons. The slaughter in the territories began as early as the spring of 1915. Tens of thousands Armenians were killed in the vilayets of Erzerum and Van. The mass terror prevailed in Bitlis, Sasun, Musha, Diarbekire. Simultaneously, the soldiers and officers of Armenian nationality who were serving in the Turkish army, were disarmed and shifted to the labour battalions, which were later destroyed. On 24 May 1915 the governments of England, France and Russia announced a joint declaration which stated that "considering these recent crimes perpetrated against humanity and civilisation, the governments of Russia, France and England united present a public manifestation to the Porte that they place personal responsibility for these crimes on all members of the Turkish authorities, and also on those local representatives who may appear to have supported similar slaughter". Within three days of this Declaration, on 27 May, Turkey adopted a law on deportation; during the summer, they expelled to the Arabian deserts all Armenian inhabitants who had survived from West Armenia, Kilikia, and also from the central territories of Turkey. The deportation was deliberately carried out in conditions under which only 10 to 25 percent of the deported would reach their "new settlements". Most would be killed in the deserts before arrival. After the capitulation of Turkey, beginning on 24 May 1915, the Allies, referring to their previous notification, brought charges against those who allegedly organized and carried out the extermination of the Armenian people. On 19 July 1919 the Supreme Military Court sentenced Talaat, Enver, Dzhemal and Nazim to death (in absentia). At this moment the process of democratization in Turkey was suspended, and the remaining accused, more than a hundred people, were soon released. Then, on 3 January 1921 the government of Mustafa Kemal Ataturk established its own Supreme Military Court which cancelled the rulings of the previous Supreme Military Court on the "so-called crimes". Thus, many organizers and participants of the genocide of the Armenian nation became national heroes, later achieving brilliant political careers in the Republic of Turkey. It was that during the regime of Ataturk that Turkism completely triumphed in all spheres of life to the present day... As a result of the genocide, of about 2,100,000 Armenians who had been living in the Ottoman Turkey until the outbreak of the First World War, only about 500,000 managed to escape by fleeing to other countries. Over one million were killed, the rest, mostly children and young women, were forced to embrace Islam and Turkism. The main lands of the Armenians, where the Armenian civilization had been evolving for thousands of years, were not only deserted by the Armenians, but they were razed; their churches and monasteries destroyed, and other buildings levelled to the ground by bulldozers. In order to conceal the intentional and organized character of the crime, the archives of the central committees of the parties Unity and Progress, Special organisation and those documents of the Ministry of the Interior and War Department which directly or implicitly pointed to the criminal activities of the leaders of the Ittihad and the government were liquidated after the autumn of 1918. Nevertheless, the newspaper reports of the Constantinople trials, as well as numerous documents from the archives of Germany, Austria, the United States, Great Britain, Russia, and other countries give unambiguous evidence that the activities of the Young Turks in relation to the Armenian people fully corresponded to what according to the Convention On Prevention and Punishment of the Crime of Genocide, adopted by the General Assembly of the UN on 9 December 1948, can be called genocide. This fact was recently recognised by the European Parliament and many countries of the world. However, Official Turkey’s confrontation with the truth continues; it still refuses to admit that it perpetrated genocide during the First World War. The truth is that, as has been noted before, Nazism and pan-Turkism have many things in common – both ideologies contain the prevailing idea about the superior race, employing terror against those who do not belong to this race. Hitler intended "to annihilate unmercifully all men, women and children of Polish origin" in order to occupy "the necessary living space". The Young Turks also were in need of "living space". For Turkey this meant land only for the Turks, on behalf of the Great Turan. Thus, in order to prevent "the inevitable separation of the Armenians in the natural run of the history", what would have become "a tombstone on the Turanian programme" they initiated extermination of the Armenian people.